Kewenangan Presiden dalam Pengangkatan Panglima TNI ditinjau dari Sistem Presidensial: The President’s Authority to Appoint the Commander of the Indonesian National Armed Forces from the Perspective of the Presidential System - Dea Arsyad (SIYASI: Jurnal Trias Politica, 2024)
The Presidential system ensures a strong position for the President in Indonesia's state system. However, in the derivative regulations of the 1945 Constitution, the position of the DPR (People's Consultative Assembly) is stronger than that of the President, as seen in the appointment of state officials. The Law No. 34 of 2004 regarding the Indonesian National Armed Forces (TNI) requires "approval" from the DPR in every proposal of a TNI Commander candidate submitted by the President. The involvement of the DPR in approving or disapproving has reduced the President's prerogative power. The purpose of this research is to determine the authority of the President in appointing the TNI Commander in the Presidential system, and the extent of the DPR's involvement in the appointment process. This article uses the normative juridical method with a statute approach and literature review as the research specification, with a descriptive analytical approach. The article concludes that there is a confusion in the use of the Presidential system in Indonesia regarding the appointment of state officials, as the DPR has the authority to approve candidates, which reduces the President's power in appointing the TNI Commander. This is in contradiction with the Constitution, which clearly states that Indonesia uses the Presidential system.